Drug Repositioning for Hand, Foot, and Mouth Disease - Ran Yan; Jiahao He; Ge Liu; Jianfeng Zhong; Jiapeng Xu; Kai Zheng; Zhe Ren; Zhendan He; Qinchang Zhu (Viruses, 2022)
Hand, foot, and mouth disease (HFMD) is a highly contagious disease in children caused by a group of enteroviruses. HFMD currently presents a major threat to infants and young children because of a lack of antiviral drugs in clinical practice. Drug repositioning is an attractive drug discovery strategy aimed at identifying and developing new drugs for diseases. Notably, repositioning of well-characterized therapeutics, including either approved or investigational drugs, is becoming a potential strategy to identify new treatments for virus infections. Various types of drugs, including antibacterial, cardiovascular, and anticancer agents, have been studied in relation to their therapeutic potential to treat HFMD. In this review, we summarize the major outbreaks of HFMD and the progress in drug repositioning to treat this disease. We also discuss the structural features and mode of action of these repositioned drugs and highlight the opportunities and challenges of drug repositioning for HFMD.